2006
DOI: 10.1007/s00066-006-1461-8
|View full text |Cite
|
Sign up to set email alerts
|

Die Rolle der interstitiellen Brachytherapie bei der Behandlung von Tumoren der Vagina und Vulva

Abstract: IBT achieved good local control without serious delayed side effects in both localizations. However, survival is limited by regional or distant metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Other authors also observed a low number of complications [9,14,18]. Jolicoeur observed acute toxicity grade 2 in all patients but late severe toxicity only in two women [18].…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…Other authors also observed a low number of complications [9,14,18]. Jolicoeur observed acute toxicity grade 2 in all patients but late severe toxicity only in two women [18].…”
Section: Discussionmentioning
confidence: 89%
“…There are only few reports in the literature concerning recurrent vulvar cancer treated with interstitial HDR brachytherapy [9,18,19]. It may be used as a "boost" or as a sole treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations